Sensory Properties of Mustard Greens Crackers (Brassica juncea L.) - Ayu Krisnawati; Ida Agustina Saidi (Procedia of Engineering and Life Science, 2022)
The purpose of the study was to determine the sensory properties of crackers by the addition of green mustard flour or green mustard paste. This research was experimental research single factor used Randomized Block Design. This treatment was the ratio of addition of green mustard flour or green mustard paste namely K0 (without the addition of green mustard flour or green mustard paste), K1 (1% green mustard flour), K2 (2% green mustard flour), K3 (3% green mustard flour), K4 (4% green mustard flour), K5 (5% green mustard flour), K6 (10% green mustard paste), K7 (15% green mustard paste), K8 (20% green mustard paste), K9 (25% green mustard paste) and K10 (30% green mustard paste). The data were analyzed using the Friedman test. The results showed that the addition of green mustard flour or green mustard paste has a significant effect on the hedonic test of color, aroma, taste, and texture of mustard crackers.